DEVELOPING SPEAKING SKILL THROUGH PRESENTATION PRACTIC PRODUCT (TRIPLE P) AT THE SECOND GRADE STUDENTS OF SMPN SEKOTONG BARAT - Tawali Tawali (Sinar Lima, 2025)
This research is aimed to develop speaking skill through the presentation Practice Product (Triple P) to develop speaking skill at second grade students of SMPN 5 Sekotong Barat in academic year 2024/2025. The objective of the study was to know how can the Presentation Practice Product (Triple P) to develop students speaking skill. This research belongs to classroom action research with 4 procedures they are planning, acting, observing, and reflecting or mix method, qualitative method and quantitative method. The technique of collecting the data was pre-test and post-test. The instrument of the research used three types of getting the data were written test in the form of multiple choice, questionnaires with 5 options they are very agree scored 5, agree scored 4, partial 3, very disagree 2, and disagree 1, and Observation sheet were students’ activities observation sheet, teacher’s activities observation sheet, and observer’s activities observation sheet. The procedure to analyze data were mean score by using formula Sudijono,2008: 43), and percentage was used according to Purwanto, 2010: 10). The result of data analysis showed that the value of pre-test was 7.1 and post-test was 8.1 so the value of -post-test is higher than the criterion of success (KKM) was 75. It means that the first cycle could achieve the criterion of success. Therefore, the research done only one cycle. It could be concluded that through presentation practice product (Triple P) could develop the students’ skill at second grade student of SMPN 5 Sekotong Barat in Academic Year 2024/2025.